Family history of arterial hypertension and central adiposity: impact on blood pressure in schoolchildren - Tatiana Aparecida Affornali Tozo; Maria Lourdes Gisi; Caroline Brand; Carla Marisa Maia Moreira; Beatriz Oliveira Pereira; Neiva Leite (BMC, 2022)
Abstract Background A family history of arterial hypertension is an important risk factor for arterial hypertension. This study aimed to verify the mediating role of high central adiposity in the relationship between family history of arterial hypertension and blood pressure in schoolchildren. Methods Cross-sectional study with 118 schoolchildren of both sexes aged between 11 and 17 years. Weight, height, waist circumference and body mass index z score were verified. Somatic maturation was predicted by age for peak growth velocity. The family history of arterial hypertension was verified and defined as hypertensive schoolchildren with systolic blood pressure or diastolic blood pressure. Mediation analysis was used with linear regression models applied by PROCESS macro for SPSS (version 22.0), with significance p < 0.05. Results It was observed that 34.7% of the students have family history of arterial hypertension, 36% of the girls and 44.2% of the boys have arterial hypertension. In girls, the relationship between waist circumference and systolic blood pressure was direct (β = 0.535 p = 0.005), and those with a family history of arterial hypertension and who had a waist circumference greater than those without a family history of arterial hypertension was significant (β = -5,437 p = 0.009). Likewise, the relationship between family history of arterial hypertension and systolic blood pressure was attenuated when waist circumference was included in the model (β = -5.544; p = 0.103), indicating waist circumference as a mediator with an influence percentage of 19%. For boys, waist circumference is not a mediator of the relationship between family history of arterial hypertension and blood pressure. Conclusions Elevated central adiposity was a mediator of the relationship between family history of arterial hypertension and high blood pressure in girls, indicating the importance of family health strategies in the prevention and management of arterial hypertension in children and adolescents.